PENDEKATAN KONTEKSTUAL DALAM PEMBELAJARAN SAINS - Mundilarto . (Jurnal Cakrawala Pendidikan, 2004)
The contextual scienceleaming strategy can be carried out to the optimum ifsupported by teachers' creativity and capability to make use ofthe potentials ofthe students, their school, and its environment The problem is whether teachers ofstudents leamiD.g science already have the capability to develop and implement a contextual learning strategy in their students. This article is written for the purpos~of increasing those teachers' knowledge and understanding ofthe afore said learning strategy in order that they can develop and to implement it in their science classes. Being contextual, it is a strategy relating instructional content withreal situations ofthe learners and encourag ing themto relate academic knowledge to its application in their lives as individuals and family or community members. Contextual learning has the following characteristics: I) emphasizing problem solving, 2) recognizing that teaching and learning need to occur in multiple context, 3) assisting students in learning how to monitor their leaming sd thattheybecomeseJf,.regu1ated leamers, 4) anchoring teach inginthe diverse life context ofstudents, 5) encouraging students to learn from each other, and 6) employing authentic assessment. Keywords: contextilal, learning science